Diagnostic accuracy of FNA to determine HPV status in HPV-associated oropharyngeal squamous cell carcinoma. (November 2022) - Morse, Ryan T.; Beaty, Brian; Scanga, Lori; Blumberg, Jeff; Patel, Samip; Yarbrough, Wendell G.; Lumley, Catherine; Hackman, Trevor; Shen, Colette; Gupta, Gaorav P.; Chera, Bhisham S.
Highlights: Initial FNA was diagnostic for malignancy in 73.6% patients. Final yield of FNA biopsies to diagnose malignancy and p16 status was 47.3%. Non-diagnostic FNA biopsy led to delay in radiation initiation. Patient costs were elevated when FNA biopsy was non-diagnostic or p16 indeterminate. Abstract: Purpose/Objective(s): Accurate diagnosis of human papillomavirus (HPV) status in oropharyngeal squamous cell carcinoma (OPSCC) affects prognosis and can alter the treatment plan. We evaluated the diagnostic accuracy of FNA biopsies to determine malignancy and HPV status in OPSCC at our institution. Methods: Pathology samples from consecutive patients with pathologically confirmed HPV-associated OPSCC who underwent FNA of a cervical lymph node during initial diagnostic work-up were retrospectively analyzed between November 2015 and August 2021. Results: Initial FNA was diagnostic for malignancy in 109/148 (73.6%) patients and non-diagnostic in 39/148 (26.4%). P16 staining of FNAs positive for malignancy showed: 54/109 (49.5%) p16 positive, 6/109 (5.5%) p16 negative, 49/109 (45.0%) p16 indeterminate. In patients with an initial non-diagnostic sampling or p16 indeterminate, repeat FNA was performed in 30/88 (34.1%) patients. Of the 30 repeat FNAs: 23/30 (76.7%) were diagnostic of malignancy and 7/30 (23.3%) remained non-diagnostic for malignancy. Of the 23 repeat FNAs diagnostic of malignancy: 16/23 (69.6%) were p16 positive and 7/23 (30.4%) were p16 indeterminate. In summary, 88/148 (59.5%) initial FNAs and 14/30 (46.7%) of repeat FNAs were non-diagnostic of malignancy or p16 indeterminate. Final yield of FNA biopsies (initial and first repeat FNA) to diagnose malignancy and p16 status was 70/148 (47.3%). Conclusions: Fine needle aspirations of lymph nodes in patients with HPV-associated OPSCC are frequently non-diagnostic for malignancy or indeterminate for p16 status, requiring repeat FNA or biopsy of the primary site. This can potentially cause treatment delay and increase morbidity and cost to the patient.